Receptors and Lethal Effect of Bacillus thuringiensis Insecticidal Crystal Proteins to the Anticarsia gemmatalis (Lepidoptera, Noctuidae). (30th September 2013) - Fiuza, Lidia Mariana; Knaak, Neiva; da Silva, Rogério Fernando Pires; Henriques, João Antônio Pêgas
Abstract : Bioassays with insecticidal crystal proteins (ICPs) from Bacillus thuringiensis have demonstrated that Cry1Aa, Cry1Ac, and Cry1Ba are the most active toxins on larvae of the Anticarsia gemmatalis . The toxins Cry1Da and Cry1Ea are less toxic, and toxins Cry2Aa are not active. Binding of these ICPs to midgut sections of the A. gemmatalis larvae was studied using streptavidin-mediated detection. The observed staining patterns showed that Cry1Aa and Cry1Ac bound to the brush border throughout the whole length of the midgut. However, the binding sites of Cry1Ba were not evenly distributed in the midgut microvilli. The in vivo assays against larvae of 2nd instar A. gemmatalis confirmed the results from the in vitro binding studies. These binding data correspond well with the bioassay results, demonstrating a correlation between receptors binding and toxicity of the tested ICPs in this insect.